2020
DOI: 10.1101/2020.07.13.196063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KHz-rate volumetric voltage imaging of the whole zebrafish heart

Abstract: Fast, high-resolution volumetric imaging of voltage transients in excitable tissues such as the heart and brain has so far been impossible. We introduce a new imaging modality based on simultaneous illumination and parallel detection of multiple planes to map voltage transients in the intact zebrafish heart at KHz-rates in 3D. The unprecedented resolution of our method enabled the observation of novel dynamics through the zebrafish atrioventricular canal.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The resulting images then correspond to a small z-stack in object space. In the simplest form of MPM, multiple non-polarizing 50:50 beamsplitters (BS) can be used in combination with different camera positions offset from the nominal focal plane (as depicted in Figure 3B) or tube lenses with different focal lengths can be used [22,[26][27][28][29][30][31][32]. To decrease the spatial footprint of this configuration, mirrors can be interspaced (Figure 3C) with the BS [12,22].…”
Section: Multiplane Imagingmentioning
confidence: 99%
“…The resulting images then correspond to a small z-stack in object space. In the simplest form of MPM, multiple non-polarizing 50:50 beamsplitters (BS) can be used in combination with different camera positions offset from the nominal focal plane (as depicted in Figure 3B) or tube lenses with different focal lengths can be used [22,[26][27][28][29][30][31][32]. To decrease the spatial footprint of this configuration, mirrors can be interspaced (Figure 3C) with the BS [12,22].…”
Section: Multiplane Imagingmentioning
confidence: 99%
“…Dual excitation of spectrally separated VSD has also been used successfully to reveal unique information about transmural heterogeneities and endocardial electrophysiology in rat hearts (Walton et al, 2010 ). Looking to the future, with the emergence of low-cost high-speed cameras, volumetric optical mapping in small-size hearts has been shown to be possible with multi-plane multi-camera parallel imaging (Sacconi et al, 2020 ).…”
Section: Multimodal Imaging Of Intracellular Ca 2+ and Membrane Potentialmentioning
confidence: 99%
“…They discovered two compounds that rescued wild-type-like APD in breakdance larvae, suggesting novel pathways for restoration of repolarization associated with hERG dysfunction. More recently, light-sheet imaging of a membrane dye in whole 14 dpf zebrafish hearts showed that E-4031 (a hERG blocker) application increases APD and induces the occurrence of frequent EAD formation (∼1 every s) ( Sacconi et al, 2020 ). These studies demonstrate the applicability of zebrafish larvae to model acquired LQTS and to conduct toxicological screening.…”
Section: Zebrafish As a Model Of Acquired Long-qt Syndromementioning
confidence: 99%